The impact of MicroRNAs (miRNAs) on the genotype of coronaviruses - Canatan, Duran; De Sanctis, Vincenzo (Acta Biomedica Atenei Parmensis, 2020)
Summar y. The beginning of 2020 has seen the emergence of COVID-19, an outbreak caused by a novel coronavirus, SARS-CoV-2, an important pathogen for humans. SARS-CoV-2 is an RNA virus containing 29891 nucleotides encoding 9889 amino acids. The genome is arranged as 5p-replicase (orf1/ab)-structural proteins [Spike (S) -Envelope (E) - Membrane (M) -Nucleocapsid (N)] −3. Viruses are obligate intracellular infectious agents that use the host cellular machinery to ensure their own fitness and survival. MicroRNAs (miRNA9) systems are potent post-transcriptional gene expression regulators that are important modulators of viral infections, and could play an important role in the treatment of viral infections. This review focuses to the genomic structure of coronaviruses, the functions of genomic proteins, the effects of micro RNA (miRNA) on virus replication and its pathogenesis.